Sme’s Readiness To Adopt Technology: A Systematic Literature Review And Future Research Directions - Wahyu, Tutus; Siwi, Tri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to identify the influence of optimism and innovation on the intention to use technology in SMEs. In addition, this research also explains existing gaps in the literature with a special focus on the SME context. A search for relevant literature was carried out using the main search terms,“Technology Readiness Index”, “SME’s”, “Technology Acceptance Model” and “e-commerce”. The study results show that there is a positive relationship between intention to use technology and positive TR constructs (optimism, innovation), perceived ease of use and perceived usefulness. Apart from that, there are moderating variables, namely gender and generation, as well as mediating variables: performance expectations, effort expectations, condition of facilities, quality of trust. education, age, income. The limitation of this research is that the researcher missed information related to the theory of readiness and acceptance of technology other than TR and TAM, so it had to be usedkeyword additions to make the research more comprehensive. This research provides practical implications, namely that it can contribute and evaluate in increasing readiness for technology adoption. This research also provides information and contributions in developing theories about TRI (Technology Readiness Index) and TAM (Technology Acceptance Model). This systematic literature review highlights important knowledge gaps that need to be explored especially in the context of technology adoption readiness for SMEs.